Chapter Unmanned Aerial Systems - Konrad, Rudin (InTechOpen, 2017)
Unmanned aerial platforms are a means to gather efficiently valuable aerial information to support the crisis manager for further tactical planning and deployment. They can provide continuous support to the coordinators and operators by scanning blocked sectors or establish an communication network. This chapter describes how aerial platforms were tailored to search and rescue (SAR) requirements, including the localisation and tracking of victims. In order to meet the end user demands, complementary platforms are proposed. A small long‐endurance solar aeroplane is used to provide the largest and fastest area coverage at the highest view, and therefore enabling the mapping functionality and potential detection of victims with operation times span up to a day. Complementary to the aeroplane, two rotary‐wing systems were deployed. A large coaxial‐quadrotor was used for outdoor delivery task and detailed close range inspection. Its ability to fly close to the terrain enables a thorough search for victims in a well‐defined sector. A smaller multicopter was used for inspection of the indoor environment. It is able for victim detection in collapsed buildings. Thus, autonomous functionality for precise localisation and positioning was developed to decrease the operator workload.